DAMPAK KONSELING TERHADAP TINGKAT KECEMASAN KLIEN DENGAN RISIKO TINGGI HIV AIDS DI DAERAH PARIWISATA SENGGIGI LOMBOK BARAT - I Putu Artawan Prayoga; Akhmad Fathoni; Muhammad Sunarto (Lembaga Penelitian dan Pendidikan Mandala, 2020)
Individuals with high risk of HIV and AIDS who come to the service center VCT (Voluntary Counseling and Testing) feel worried or anxious that he has contracted HIV so he wants to know about his condition. They are usually worried or anxious about the implications of AIDS itself physically, psychologically, spiritually and socially namely the stigma and discrimination of society. Aim: this study was to determine the effect of counseling on changing anxiety levels of clients at high risk of HIV and AIDS. Methods: The design of this study was pre-experiment with one group pre-post-test design approach because before being given treatment, the client first assessed the level of anxiety, then after being given treatment the level of anxiety was re-examined, whether decreased anxiety level or not. The instrument used in this study was the HARS questionnaire. The instrument used in this study was the HARS questionnaire. The sampling technique used was purposive sampling with 21 samples. Univariate data analysis used is in the form of narration, frequency and percentage distribution tables, and bivariate analysis using parametric data analysis techniques, namely t-test dependent. Result: This study shows that from 21 respondents before and after counseling, they have a difference of 6.19 with a standar deviation of 4.98. The p value of 0.000 indicates that the value is smaller when comparing the alpha value of 5% (0.05), meaning that there are differences in anxiety before and after counseling, so it can be concluded that there is an influence of spiritual counseling on the level of anxiety in high risk clients of HIV and AIDS in the area Senggigi medical tourism center. Conclusion: provision of counseling that has been going well in order to be maintained and enhanced by holding professional counselors training regularly and continuously.